The performance of nursing students in a tele-health service during the COVID-19 pandemic - Luana Daiane Guimarães Lima; Jamila Geri Tomaschewski-Barlem; Gabriela do Rosário Paloski; Edison Luiz Devos Barlem; Laurelize Pereira Rocha; Janaína Sena Castanheira (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To identify the experiences of nursing students working in a telehealth service to fight the COVID-19. Method: Qualitative, exploratory, and descriptive study, addressing 31 undergraduate nursing students at a Federal University located in the extreme south of Brazil. Data were collected in October 2020 using an online questionnaire. Textual discourse analysis was used to interpret data. Results: The students identified facilities, weaknesses, and potentialities of a telehealth service, verifying that it is a strategy that favors the development of skills and competencies during the training of students and to fight the COVID-19 pandemic. Conclusion: The results reveal the students' experiences in a telehealth service designed to fight the COVID-19, showing the importance of including this service in the routine of healthcare services.